2019
DOI: 10.1108/jeim-06-2018-0132
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of blockchain technology

Abstract: Purpose Although blockchain is often discussed, its actual diffusion seems to be varying for different industries. The purpose of this paper is to explore the blockchain technology diffusion in different industries through a combination of academic literature and social media (Twitter). Design/methodology/approach The insights derived from the academic literature and social media have been used to classify industries into five stages of the innovation-decision process, namely, knowledge, persuasion, decision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(46 citation statements)
references
References 97 publications
(123 reference statements)
1
45
0
Order By: Relevance
“…These new technologies used in digital transformation can be cloud, blockchain, mobile, AI, Internet of Things and other smart technologies (Duan et al, 2019;Dubey et al, 2020;Hughes et al, 2019;Ismagilova et al, 2019;Wamba and Queiroz, 2020). The usage of technology for digital transformation is determined by organization's attitude towards the technology, perceived usefulness and perceived ease of use (Berlak et al, 2020;Grover et al, 2019). Organizations has been significantly engaged in digital transformation (Burton-Jones et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These new technologies used in digital transformation can be cloud, blockchain, mobile, AI, Internet of Things and other smart technologies (Duan et al, 2019;Dubey et al, 2020;Hughes et al, 2019;Ismagilova et al, 2019;Wamba and Queiroz, 2020). The usage of technology for digital transformation is determined by organization's attitude towards the technology, perceived usefulness and perceived ease of use (Berlak et al, 2020;Grover et al, 2019). Organizations has been significantly engaged in digital transformation (Burton-Jones et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For exploring some of these propositions (Proposition 1a to Proposition 4b), two complementary approaches, academic literature review and social media analytics, suggested by Grover, , for determining diffusion of blockchain in different industries had been used. Literature review is a better approach for tracing features and challenges of the technology (in this article technology under consideration is AI) within industry sector (in this article industry sector under consideration is OM), whereas for tracing practical implementation of the use cases social media is a better approach (Grover et al, 2019). Banomyong, Varadejsatitwong and Oloruntoba (2019) had pointed out literature review identifies main research themes from the literature available.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these characteristics, blockchain technology greatly enhances credibility, reduces the cost of business cooperation, and has broad application prospects. e study in [4] believes that blockchain technology has proliferated in almost all industries, but to varying degrees. Specifically, he found that some industries such as transportation, communications, electricity, and new energy have a high degree of technological integration and a wide range of application scenarios.…”
Section: Literature Reviewmentioning
confidence: 99%
“…e study in [28] introduces a new short-term electricity price forecasting approach called SASVQR, which is based on support vector quantile regression (SVQR) optimized by simulated annealing algorithm. e study in [29] solved the problem of increasing the energy efficiency of urban electrical networks based on identifying factors affecting power 4 Complexity consumption, developed a forecasting model on the basis of seasonal schedules of electricity consumption by household consumers, and proposed a control algorithm based on the proposed seasonal power consumption schedules by household consumers. e above literature collates and discusses various methods of measuring power demand and supply, so as to predict the gap between electricity supply and electricity demand.…”
Section: Literature Reviewmentioning
confidence: 99%
“…First of all, a number of research studies have been conducted to assess the blockchain effect on organisational activities and examine the adoption process of blockchain technologies across various industries (Grover et al, 2019). As a matter of fact, the majority of such studies have been done in the framework of the functionalist paradigm and in relation to SCM and logistics.…”
Section: Technology Adoption Theoriesmentioning
confidence: 99%